Intuitive UX In a Redesign of Ullmanstolen - Gustafsson, Lucas; Lackner, Olga (My University, 2024)
Acknowledgements This master's thesis was pursued as part of the master's programme of Industrial Design Engineering at the Industrial and Materials Science department at Chalmers University of Technology. The thesis would not have been possible without the support of our examiner and supervisor Sanna Dahlman, who challenged our ideas and encouraged exploration throughout the process, and without whom the narrative of this work would not have come together as well as it did. We would also like to thank the company EU Ergonomiutveckling AB for contribution of knowledge on the subject and valuable insights provided. Further we extend thanks to our chair and programme director for continued support throughout the thesis and to our opponents, who asked very insightful questions at the thesis presentation and provided thoughtful feedback on the report as well as a fresh perspective on the topic. Abstract Office work has gone through changes in the past decades, with office chairs adapting, adding more controls to provide better ergonomic support. But more adjustments have resulted in a lack of understanding of how to correctly use chairs, which can negate the intended benefits and harm the user’s posture. This master thesis aims to improve usability of the controls, based on an investigation of users' current understanding of the settings and drawing conclusions on how this can guide the design of the controls. The chair this research focuses on, Ullmanstolen, was launched around forty years ago and therefore provides a good starting point for adapting to new types of working environments. A design guide is established through a user study and user evaluation. To address the lack of understanding of adjustable chair settings, a design of clearly visible, distinct controls adhering to placement conventions and user’s mental models is vital, showcased in a redesign of Ullmanstolen.